Stylistic Analysis on William Blake's The Little Boy Lost - Olyvia Vita Ardhani (Jadila: Journal of Development and Innovation in Language and Literature Education, 2020)
This research presented the stylistic analysis of a poem by William Blake, The Little Boy Lost. The poem was chosen as it becomes Blake's one of well-known poems in his Song of Innocence. Moreover, this poem uses simple structure and dictions, but it conveys a profound meaning. This research aimed: (1) to discover how the language level in the poem used and (2) to find out the interpretation of the poem. The stylistic analysis aimed at observing the meaning of either literary or non-literary text by the language device used. The researcher conducted a data population method in analyzing the poem. There were four language levels to achieve the goal; they were phonological, graphological, lexical, and syntactic level (Verdonk: 2002). In the phonological level, assonance, consonance, and alliteration were used to emphasize important words. In the graphological level, the comma in the last line of stanza 1 is prominent to distinguish the different speakers. In the lexical level, metaphor was used to voice the little boy's hopes to find enlightenment to get out of his difficulties. Meanwhile, symbolism conveys a deeper meaning than the literal meaning. In the syntactic level, the tenses switching used to emphasize the different speakers and the comma in the graphological level; and the word repetition used to create the little boy's sense of innocence.